On the need for changes in the act – law on higher education and science in the context of canon law regulations concerning higher education - Kilanowski, Igor M. (Prawo Kanoniczne, 2024)
The article points to the need to update Polish legal regulations, which are currently out of step with the modern realities of the higher education and science system, as well as the principles arising from canon law and the Concordat. It presents the legal basis for relations between the state and the Church, as set out in the Polish Constitution, religious laws, and the 1993 Concordat. It is pointed out that the current agreement between the Government of the Republic of Poland and the Polish Episcopal Conference of 1999 is outdated and needs to be adapted to the 2018 Act on Higher Education and Science. The study highlighted problems related to the recognition of degrees and titles awarded by church higher education institutions, the evaluation of the quality of scientific activity, the assessment of the quality of education, and the running of doctoral schools. The author critically analyzes the current division of scientific fields and disciplines, proposing, among other things, the separation of canon law as an independent scientific discipline within the field of legal sciences and the reorganization of the relationship between the classifications of the Holy See and Poland. The article emphasizes that legislative changes should respect the principle of the state's ideological neutrality, while promoting cooperation between the state and the Church for the common good. The author also proposes the development of a new executive agreement to the Concordat and greater involvement of church and academic circles in the reform process, particularly with regard to the proper application of canon law in entities that are subject to it through ecclesiastical authority. Quoting Pope Francis, he points to the need for courage in engaging in dialogue and actions aimed at the development of universities and church faculties with a Christian ethos, and more broadly, church sciences in Poland. The author critically analyzes the current division of scientific fields and disciplines, proposing, among other things, the separation of canon law as an independent scientific discipline within the field of legal sciences and the reorganization of the relationship between the classifications of the Holy See and Poland. The article emphasizes that legislative changes should respect the principle of the state's ideological impartiality and, at the same time, promote cooperation between the state and the Church for the common good. The author also proposes the development of a new executive agreement to the Concordat and greater involvement of church and academic circles in the reform process, particularly with regard to the proper application of canon law provisions.